2020
DOI: 10.1128/iai.00338-20
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis Induces Differentiation of Immune-Aberrant Dendritic Cells from Murine Bone Marrow-Derived Stem Cells

Abstract: Enterococcus faecalis (E. faecalis), long implicated in serious systemic infections and failure of root canal treatment, is a persistent inhabitant of oral periapical lesions. Dendritic cells (DCs) and other innate immune cells patrol the oral mucosa for infecting microbes. Dendritic cells are efficient at capturing microbes when immature, whereupon they can transform into potent antigen-presenting cells upon full maturation. Autophagy, a sophisticated intracellular process first described for elimination of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The ability of E. faecalis to downregulate the immune and inflammatory responses indicated a high virulence of the strain [46]. Consistent with previous studies, E. faecalis influenced bone marrow stem cell differentiation by promoting CD11c-positive dendritic cells with aberrant immune functions retaining the capability of proinflammatory cytokine induction [47]. Another study showed that E. faecalis in high doses slowed healing and suppressed the expression of inflammatory cytokines in a mouse model [48].…”
Section: Discussionsupporting
confidence: 86%
“…The ability of E. faecalis to downregulate the immune and inflammatory responses indicated a high virulence of the strain [46]. Consistent with previous studies, E. faecalis influenced bone marrow stem cell differentiation by promoting CD11c-positive dendritic cells with aberrant immune functions retaining the capability of proinflammatory cytokine induction [47]. Another study showed that E. faecalis in high doses slowed healing and suppressed the expression of inflammatory cytokines in a mouse model [48].…”
Section: Discussionsupporting
confidence: 86%
“…Infection was maintained throughout the study by adding an additional dose of E. faecalis at day 6 with the same MOI. The rationale of using an MOI of 1 was to mimic chronic infection for a prolonged time with a low quantity of bacteria; a similar MOI was used for examining E. faecalis infection of BMSC-derived dendritic cells [18]. Infection of the already differentiated macrophages (post-M0 + E. faecalis) was performed at day 6 with an MOI of 1, to correlate and compare the effect of E. faecalis on macrophages before and after their differentiation.…”
Section: Bacterial Preparation and Infection Of Bmscsmentioning
confidence: 99%
“…Interestingly, due to its resistance to antiseptics and disinfectants used in dental hygiene, E. faecalis is described as an essential cause of endodontic treatment failure, isolated in up to 77% of chronic and persistent periapical lesions cases [ 11 ]. In persistent intra-radicular E. faecalis infections, interaction with the host immune cells can lead to apical periodontitis that does not heal and can generate tissue destruction with bone resorption [ 12 , 13 ]. In this way, E. faecalis is considered the most significant species found in cases of duct systems with periradicular lesions [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%